Tribological properties of aluminium reinforced by TiCN nanosized powder. (April 2020) - Kolev, M; Valkov, S; Lazarova, R; Petrov, P; Dimitrova, R; Dyakova, V
Abstract: The work is aimed at investigating the tribological properties of aluminium surface modified by electron beam with TiCN nanoparticles as a reinforcing phase. In the course of study, the microstructure is observed and the surface of treated and untreated specimens are tested and compared in order to determine the influence of the reinforcing TiCN phase on the coefficient of friction, the friction force, and the linear mass wear. The tribological properties are evaluated by the pin-on-disk technique in a lubricating medium. The TiCN nanoparticles embedded in the aluminium matrix are obstacles to any dislocation motion, which improves the tribological properties of the samples' surfaces. The acting wear mechanisms are discussed.